Prevalence and determinants of vaccination intention towards routine immunizations in university students: a systematic review and meta-analysis - Ilaria Mussetto; Maria Chiara Bernucci; Anna Ewa Kaminska; Claudia Isonne; Antonio Sciurti; Giuseppe Migliara; Erika Renzi; Azzurra Massimi; Carolina Marzuillo; Corrado De Vito; Paolo Villari; Valentina Baccolini (BMC Public Health)
Abstract Background It is well known that, to be effective, vaccination programs require a high and consistent population uptake. Nevertheless, vaccine coverage is often insufficient. University students occupy a unique position within the broader population: they are highly mobile and socially active individuals who serve as influential figures among their peers and younger age groups, making them an ideal target for educational campaigns. Methods This review (CRD42022309724) quantified the vaccination intention rates for routine immunizations in university students and systematically examined the determinants of vaccination acceptance. Cross-sectional studies that analyzed vaccination intention for at least one routine immunization using multivariable logistic regression were included. We used random-effects models to calculate the pooled proportions of vaccination intention. Determinants were categorized into contextual factors (such as socio-demographic, economic and cultural factors), individual/group factors (such as knowledge, awareness, peer opinions, infection risk perceptions) and vaccine-specific issues (such as vaccine effectiveness and vaccination policies). Results Thirty-six articles were included: 29 on the human papilloma virus (HPV) vaccine and seven on the influenza vaccine. The pooled proportion of students intending to get vaccinated was 54% (95% CI: 47–60%) for HPV and 43% (95% CI: 26–61%) for influenza. The strongest positive determinants were individual/group factors, such as higher knowledge and awareness, pro-vaccine peer opinions, positive personal experience with vaccinations, and higher risk perception for HPV infection, and higher risk perception for infection and previous vaccination history for influenza. By contrast, contextual influences played a minor role in both vaccinations, while vaccine-specific concerns, particularly about costs and availability, negatively influenced intention for both vaccines. Conclusions Given the suboptimal rates of vaccination intention towards HPV and influenza vaccine that we found, addressing key determinants, such as awareness of infection risks and perception of vaccination benefits, is essential to increase vaccination acceptance in university students and to achieve high vaccination coverage.